2010
DOI: 10.5251/ajsir.2010.1.3.656.666
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic Pumping of Williamson fluid through a porous medium in a horizontal channel with heat transfer

Abstract: In this paper, we investigated the interaction of heat transfer with peristaltic pumping of a Williamson fluid through a porous medium in a planar channel, under the assumptions of low Reynolds number and long wavelength. The flow is investigated in a wave frame of reference moving with velocity of the wave. The perturbation series in the Weissenberg number ( 1 We < ) was used to obtain explicit forms for velocity field, pressure gradient and friction force per one wavelength. The effects of Weissenberg number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Peristaltic motion of Williamson fluid through a channel enclosed by permeable wall is significant in Biology and medicine; in this regard Vajravelu et al studied the peristaltic motion of non-Newtonian fluid through asymmetric channels along porous wall by means of various phase and amplitude, and also studied the manipulation of different wave structures on the fluid flow model [8]. By considering the approximation of long wave length and small Reynolds number the peristaltic pumping of Williamson fluid in a planar channel was investigated by Vasudev et al and they studied the flow in wave framework which is moving with speed of wave [9]. Nadeem et al developed a model for the transport of Williamson fluid in an annular region [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peristaltic motion of Williamson fluid through a channel enclosed by permeable wall is significant in Biology and medicine; in this regard Vajravelu et al studied the peristaltic motion of non-Newtonian fluid through asymmetric channels along porous wall by means of various phase and amplitude, and also studied the manipulation of different wave structures on the fluid flow model [8]. By considering the approximation of long wave length and small Reynolds number the peristaltic pumping of Williamson fluid in a planar channel was investigated by Vasudev et al and they studied the flow in wave framework which is moving with speed of wave [9]. Nadeem et al developed a model for the transport of Williamson fluid in an annular region [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peristaltic flow of a Williamson fluid has been discussed by . Vasudev et al (2010) studied the peristaltic pumping of a Williamson fluid through a porous medium considering heat transfer. Cramer et al (1968) showed that this model fits the experimental data of polymer solutions and particle suspensions better than other models.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the HPM [25][26][27], Eq. (7), (8) and (9) 2 2 2 2 0 0 24 1 2 2 1 1 2 2 0 1 2 22 1 0 3 2 1 1 1 0 2 3 2 0 1 2 1 0 4 1 2 1 12 24 3 41 1 1 2 1 2 4 respectively. It is seen, from Figure 2 and 3, that the stream function decreases with the increase of M , whereas it increases as 0  increases, respectively.…”
Section: Methods Of Solutionsmentioning
confidence: 99%
“…They called the blood space as channel and tissue space as the porous layer. The effect of heat transfer on peristaltic transport of Newtonian fluid through a porous medium in an asymmetric vertical channel was discussed by Vasudev et al, [9]. Also, heat and mass transfer of MHD unsteady Maxwell fluid flow through porous medium past a porous flat plate was analyzed by El-dabe et al, [10].…”
Section: Introductionmentioning
confidence: 99%